Sex-Specific Control of Human Heart Maturation by the Progesterone Receptor. Issue 16 (8th March 2021) - Sim, Choon Boon; Phipson, Belinda; Ziemann, Mark; Rafehi, Haloom; Mills, Richard J.; Watt, Kevin I.; Abu-Bonsrah, Kwaku D.; Kalathur, Ravi K.R.; Voges, Holly K.; Dinh, Doan T.; ter Huurne, Menno; Vivien, Celine J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Despite in-depth knowledge of the molecular mechanisms controlling embryonic heart development, little is known about the signals governing postnatal maturation of the human heart. Methods: Single-nucleus RNA sequencing of 54 140 nuclei from 9 human donors was used to profile transcriptional changes in diverse cardiac cell types during maturation from fetal stages to adulthood. Bulk RNA sequencing and the Assay for Transposase-Accessible Chromatin using sequencing were used to further validate transcriptional changes and to profile alterations in the chromatin accessibility landscape in purified cardiomyocyte nuclei from 21 human donors. Functional validation studies of sex steroids implicated in cardiac maturation were performed in human pluripotent stem cell–derived cardiac organoids and mice. Results: Our data identify the progesterone receptor as a key mediator of sex-dependent transcriptional programs during cardiomyocyte maturation. Functional validation studies in human cardiac organoids and mice demonstrate that the progesterone receptor drives sex-specific metabolic programs and maturation of cardiac contractile properties. Conclusions: These data provide a blueprint for understanding human heart maturation in both sexes and reveal an important role for the progesterone receptor in human heart development.